Early identification and intervention matters: A comprehensive review of current evidence and recommendations for the monitoring of bone health in patients with cancer. (December 2017) - Brodowicz, Thomas; Hadji, Peyman; Niepel, Daniela; Diel, Ingo
Highlights: Bone metastases and skeletal-related events (SREs) are common in advanced cancer. Agents such as denosumab and bisphosphonates can prevent SREs. Early detection of bone metastases is vital for early intervention. Across tumor types, guidelines differ in their recommendations on bone assessment. Regular bone health monitoring is important in patients with advanced cancer. Abstract: Bone metastases are common in patients with advanced solid tumors, and many individuals experience debilitating skeletal-related events (SREs; e.g. pathologic fracture, hypercalcemia, radiotherapy or surgery to bone, and spinal cord compression). These events substantially affect disease outcomes, including survival and quality of life, and healthcare systems. Plain radiography is the most widely used imaging modality for the detection of bone metastases; skeletal scintigraphy, computed tomography, positron emission tomography and magnetic resonance imaging offer greater sensitivity but their use in routine practice is restricted by high costs and limited availability. Biomarkers of bone turnover may also have a role in the early detection of bone metastases and can provide valuable prognostic information on disease progression. SREs can be delayed or prevented using agents such as the receptor activator of nuclear factor kappa B ligand (RANKL) inhibitor, denosumab, and bisphosphonates. Painful bone metastases can be treated with radiofrequency ablation, radiotherapy, or radionuclides such as radium-223 dichloride, which has been shown to delay the onset of SREs in men with castration-resistant prostate cancer. Close monitoring of bone health in patients with advanced cancer may lead to early identification of individuals with bone metastases who could benefit from early intervention to prevent SREs. This review examines current guideline recommendations for assessing and monitoring bone health in patients with advanced cancer, use of biomarkers and treatment of patients with bone metastases. The emerging evidence for the potential survival benefit conferred by early intervention with denosumab and bisphosphonates is also discussed, together with best practice recommendations.